1995
DOI: 10.1128/jvi.69.12.7612-7621.1995
|View full text |Cite
|
Sign up to set email alerts
|

Binding of cellular repressor protein or the IE2 protein to a cis-acting negative regulatory element upstream of a human cytomegalovirus early promoter

Abstract: We have previously shown that the human cytomegalovirus early UL4 promoter has upstream negative and positive cis-acting regulatory elements. In the absence of the upstream negative regulatory region, the positive element confers strong transcriptional activity. The positive element contains a CCAAT box dyad symmetry and binds the cellular transcription factor NF-Y. The effect of the negative regulatory element is negated by the viral IE2 protein (L. Huang, C. L. Malone, and M. F. Stinski, J. Virol. 68:2108, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 59 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…The selection may result from IE2 binding directly to sites in the viral genome or to host proteins (or another viral protein) that bind to specific sites in the viral promoter. A crs-like sequence to which IE2 is known to bind is not located in or nearby many of the IE2-activated promoters, but non-crs-like elements can also be bound by IE2 as has been described for HCMV early promoters [55,56]. Alternatively, IE2 might bring about transcription from a set of weakly active viral promoters as a consequence of the onset of viral DNA replication that rendered the genome more accessible to host GTF that interact with IE2.…”
Section: Discussionmentioning
confidence: 99%
“…The selection may result from IE2 binding directly to sites in the viral genome or to host proteins (or another viral protein) that bind to specific sites in the viral promoter. A crs-like sequence to which IE2 is known to bind is not located in or nearby many of the IE2-activated promoters, but non-crs-like elements can also be bound by IE2 as has been described for HCMV early promoters [55,56]. Alternatively, IE2 might bring about transcription from a set of weakly active viral promoters as a consequence of the onset of viral DNA replication that rendered the genome more accessible to host GTF that interact with IE2.…”
Section: Discussionmentioning
confidence: 99%
“…IE2 86 can interact with itself and the viral 75 kDa early protein (UL84), as well as with the components of the basal transcription complex (TBP and TFIIB), several TBP-associated factors, and specific transcription factors and products of the tumor suppressor genes p53 and Rb (Caswell et al, 1993;Chiou et al, 1993;Choi et al, 1995;Furnari et al, 1993;Hagemeier et al, 1992;Jupp et al, 1993;Lang et al, 1995;Lukac et al, 1994Lukac et al, , 1997Schwartz et al, 1996;Scully et al, 1995;Sommer et al, 1994;Spector and Tevethia, 1994;Speir et al, 1994;Yoo et al, 1996). IE2 86 can also bind to DNA in a site-specific but sequence-tolerant manner (Arlt et al, 1994;Cherrington et al, 1991;Huang and Stinski, 1995;Liu et al, 1991;Pizzorno and Hayward, 1990;Rodems et al, 1998;Schwartz et al, 1994;Scully et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that IE86 alone strongly activates the UL4 and UL112-113 early genes in transiently transfected cells (5,27,42) while the IE72 protein can act synergistically with IE86 to activate these genes (5,25,45,47,62). The IE86 protein has been shown to bind to the cis-acting negative regulatory element on the UL4 promoter and negate its repressive effect (18). Transactivation of the UL112 gene is mediated through an interaction between IE86 and the cellular transcription factor CREB (1,29,30).…”
mentioning
confidence: 99%